Pengaruh Kedisiplinan Kerja, Beban Kerja dan Komitmen Organisasi Terhadap Kinerja Perawat Pada Rumah Sakit Umum Daerah (RSUD) Lombok Timur - Imammul Mauladi Akbar; Suryatni, Mukmin (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This research aims to determine the influence of each variable of Work Discipline (X1) Workload (X2) and Organizational Commitment (X3) on Performance (Y). The type of research used in this study is Asositive Causal. The data collection method uses the census method with a population of 58 respondents. The type of data used in this study is quantitative data. Testing in this study uses the Multiple Linear Regression Analysis model consisting of the F Test, t Test, and R2 Test. Before conducting the Multiple Linear Regression test, an instrument quality test was first carried out consisting of the Validity and Reliability Test and the Classical Assumption Test consisting of the Normality, Multicollinearity, and Heteroscedasticity Tests to determine whether or not there are violations of the classical assumptions. Data analysis techniques using SPSS Version 25. The results of the study show that: (1) Work Discipline Has a Positive and Significant Influence on Performance. (2) Workload Has a Negative and Significant Influence on Performance (3) Organizational Commitment Has a Positive and Significant Influence on Performance. The research coefficient value shows that work discipline has a stronger influence on performance.